PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DISERTAI MEDIA GAMBAR TERHADAP KETERAMPILAN PROSES SAINS DASAR DAN HASIL BELAJAR BIOLOGI SISWA KELAS VII MTs AL-RAISIYAH SEKARBELA - Oki Prayoky; Baiq Mirawati (Bioscientist : Jurnal Ilmiah Biologi, 2014)
This study aims to determine the effect of STAD type cooperative learning model along with the image media to the basic science process skills and biology learning outcomes of students of class VII MTs Al-Raisiyah Sekarbela. The type of research used is quasi experimental research (quasi experiment). The population in this research is all students of class VII MTs Al-Raisiyah Sekarbela. The sample used in this study were students of class VIIB totaling 22 people as an experimental class and students of class VIIA which amounted to 22 people as a control class. Sampling in this research using purposive sample technique. The data of the basic science process of the students was analyzed using descriptive statistics. The results showed 85% of experimental class students have basic science process skills with very good category, 75% others with good category. While in the control class, 71% of students had basic science process skills with good category, 57% others with less good category. Data of learning result in this research is taken by giving the initial test and final test to the sample class student. Data collection techniques use objective tests that have been tested for validity and reliability. Data analysis technique using t-test test formula. The result of the final test showed that the average of experiment class is 73,22 and control class is 71,45. The result of data analysis shows thitung equal to 3,72 and ttable 2,021. Obtained thitung > ttable at 5% significance level and degrees of freedom of 44, so that Ha accepted or no influence STAD type cooperative learning model along with the media images of student learning outcomes. The conclusion in this research is that there is influence of STAD type cooperative learning model along with the picture media to basic science process skill and biology learning result of grade VII student of MTs Al-Raisiyah Sekarbela.